Bike recommender system / Muhammad Zabidi Mohd Zain … [et al.] - Mohd Zain, Muhammad Zabidi; Mokhsin @ Misron, Mudiana; Shaffiei, Zatul Amilah; Yacob @ Jusoh, Mohd Ismail; Sanusi, Yus Mohd Amirrul Asraf (Research Innovation Business Unit, 2014)
Recommender systems or recommendation systems are a subclass of information filtering system that seek to predict the ‘rating’ or ‘preference’ that user would give to an item. The method that has been applied for this project is a Prototype Model consisting of 1) First stage - initial requirement: where the researcher has collected all the data related to the system. The information may come from informal interview, observation, journals and books. 2) The second stage designing: where the researcher has designed the system based on customers requirement. 3) The third stage - is prototyping: where the researcher designed the prototype, system based on the users need. 4) The fourth stage - evaluation: where the user will evaluate if the system meets their need. 5) The fifth stage: Comment review where the researcher will review the users comment in order to improve and update the system. Stage 2,3,4,5, will be done repeatedly to fulfilling the user’s requirement. 6) The sixth stage development: where the system will be developed. 7) The seventh stage Maintenance: where the system will be maintained by the administrator of the system. This project has three objectives which are 1) to analyse the data of the motorcycle that available in the market. 2) To design a Bike Recommender System and 3) to develop a working prototype of Bike Recommender System. This project is targeted at those who want to buy a motorcycle that is available in Malaysia market. Hence, the system has two types of search features. User can search the motorcycle based on the requirement for instance, budget. Another type of search is when the user can continue to obtain the brand they want. Under that brand, they can go through all design models.